Carbon Pricing Policy and Business Adaptation Strategies in the Energy Sector in Indonesia - Virginia Amelia Supranta; Roxane Darlene Permatasari (Advanced Business Journal, 2025)
This study investigates the intersection of carbon pricing policies and business adaptation strategies within Indonesia’s energy sector. It aims to understand how firms respond to regulatory shifts and the implications for sustainable development. The research employs a mixed-methods approach, combining qualitative interviews and focus groups with quantitative surveys and economic performance indicators. This methodology enables a comprehensive analysis of corporate responses to carbon pricing and the effectiveness of policy implementation. The findings reveal that while carbon pricing incentivizes sustainable practices and technological innovation, its impact varies significantly across firms. Larger companies tend to adapt more effectively, whereas smaller enterprises face financial and operational challenges. The study underscores the importance of complementary policies, public engagement, and equity considerations in ensuring successful transitions to low-carbon operations. This research contributes to the limited empirical literature on carbon pricing in Southeast Asia, offering insights into Indonesia’s unique policy landscape. It highlights the need for tailored strategies that align economic, environmental, and social dimensions, thereby enhancing the resilience of the energy sector under climate policy frameworks.